24th European Microwave Conference, 1994 1994
DOI: 10.1109/euma.1994.337217
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Coplanar Capacitor Models and Verification Up to 67GHz for (M) MIC Circuit Design

Abstract: ABSEACTThe IMST has recently built up a library with recently more than 18 coplanar elements for CAD applications (2), (3). The theory of the parametric models is based on a quasi static 3D Finite Difference formulation (1). Naghed also introduced in (1) the model of a coplanar interdigital capacitor and presented the verification of this element up to 25GHz. Beyond 40GHz and for long fingers these simulation results diverge from measured data. This paper will report on the enhanced coplanar IDC model and 2 ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Most of these studies concentrated on the design and analysis of microstrip interdigital capacitors. Very few tried to study CPW IDCs [15][16][17]. A 3D static finite-difference method (FDM) was used in [15] to characterize the CPW IDC and other CPW discontinuities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these studies concentrated on the design and analysis of microstrip interdigital capacitors. Very few tried to study CPW IDCs [15][16][17]. A 3D static finite-difference method (FDM) was used in [15] to characterize the CPW IDC and other CPW discontinuities.…”
Section: Introductionmentioning
confidence: 99%
“…A -network of three capacitors was used to model the CPW IDC. A modified model that consists of Ncoupled lines in a coplanar environment was used to model the CPW IDC in [16]. Full details of this technique are not available in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The configuration used to characterize the microwave properties of our PST films is based on the design proposed by Kulke et al,20 shown in Fig. 2.…”
Section: Design and Simulation Of High Frequency Test Structuresmentioning
confidence: 99%
“…3, is similar to that used by Kulke et al 20 but includes the impedances due to overlap of the top and bottom electrodes and also a resistance in parallel with the PST capacitance to account for the dielectric loss. R TE , R BE , L TE , and L BE are the resistances and inductances of the top and bottom electrodes in the MIM stack, while R PST and C PST are the resistance and capacitance of the PST thin film.…”
Section: Design and Simulation Of High Frequency Test Structuresmentioning
confidence: 99%